Precise Prediction of Optical Performance for Near Infrared Instrument Using Adaptive Fitting Line - Kyeongyeon Ko; Jeong-Yeol Han; Jakyoung Nah; Heeyoung Oh; In-Soo Yuk; Chan Park; Moo-Young Chun; Jae Sok Oh; Kang-Min Kim; Hanshin Lee; Ueejeong Jeong; Daniel T. Jaffe (Journal of Astronomy and Space Sciences, 2013)
Infrared optical systems are operated at low temperature and vacuum (LT-V) condition, whereas the assembly and alignment are performed at room temperature and non-vacuum (RT-NV) condition. The differences in temperature and pressure between assembly/alignment environments and operation environment change the physical characteristics of optical and opto-mechanical parts (e.g., thickness, height, length, curvature, and refractive index), and the resultant optical performance changes accordingly. In this study, using input relay optics (IO), among the components of the Immersion GRating INfrared Spectrograph (IGRINS) which is an infrared spectrograph, a simulation based on the physical information of this optical system and an actual experiment were performed; and optical performances in the RT-NV, RT-V, and LT-V environments were predicted with an accuracy of 0.014±0.007 λ rms WFE, by developing an adaptive fitting line. The developed adaptive fitting line can quantitatively control assembly and alignment processes below λ/70 rms WFE. Therefore, it is expected that the subsequent processes of assembly, alignment, and performance analysis could not be repeated.